ACTIVITY OF NONI EXTRACT (Morinda citrifolia L.) AS A BIOFUNGICIDE AGAINST THE GROWTH OF THE FUNGUS Fusarium oxysporum IN VITRO - Puspitasari, Etika Dyah; Matsjeh, Sabirin; Mardiah, Ainun; Juni Lestari, Tri Tunggal; Kumalasari, Dewi; Kartika Sari, Prita Anggraeni (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
Fusarium oxysporum is a fungus that attacks various plants and causes wilting. Several plants, including bananas, have experienced a decrease in productivity due to the Fusarium fungus. This research aims to determine the effect of the whole plant of noni plants (fruits, leaves, and twigs), methanol extract, and ethyl acetate on the growth of fusarium fungi. To determine the optimal extract concentration to inhibit fungal growth. This research is a factorial study with independent variables in the form of extract, ingredients (fruit, leaves, and twigs), and differences in concentration. The activity of the extract as a biofungicide was analyzed based on the fungal growth inhibition zone. The results were analyzed using Anava and continued with the Duncan test. The research results show that methanol extract and ethyl acetate extract of noni have the potential as bio fungicides for the fungus Fusarium oxysporum. Noni fruit ethyl acetate extract at a concentration of 80% is optimum for inhibiting the growth of Fusarium oxysporum